Emanuel Syndrome: first case reported in Mexico - Soto-Brambila, Ada Paloma; Marín-Medina, Alejandro; Michel-Ocampo, Miguel; Figuera-Villanueva, Luis Eduardo; Rivero-Moragrega, Paloma (Investigación Clínica, 2018)
Emanuel Syndrome is a rare genomic syndrome characterized by a supernumerary derivative 22 chromosome, acquired through an inherited chromosomal imbalance of translocation (11;22). It is characterized by severe mental retardation, facial dysmorphia, genitourinary anomalies and cardiac birth defects. We report the case of a 3-yearold girl who was born with a cleft palate, bilateral hip dysplasia and patent ductus arteriosus. The patient presented with a delay in her neurocognitive development, which prompted a genetic evaluation to be performed, demonstrating a supernumerary derivative (22) t(11;22). In the familial assessment, the mother and maternal grandmother’s karyotype revealed a balanced t(11;22). The clinical manifestations, genetic analysis and the inheritance pattern are consistent with the diagnosis of Emanuel syndrome. This is the first reported case of this syndrome in Mexico.